2012
DOI: 10.1007/s11120-012-9729-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of variable fluorescence measurements of phytoplankton communities with cyanobacteria

Abstract: Excitation–emission fluorescence matrices of phytoplankton communities were simulated from laboratory-grown algae and cyanobacteria cultures, to define the optical configurations of theoretical fluorometers that either minimize or maximize the representation of these phytoplankton groups in community variable fluorescence measurements. Excitation sources that match the photosystem II (PSII) action spectrum of cyanobacteria do not necessarily lead to equal representation of cyanobacteria in community fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 43 publications
3
60
1
3
Order By: Relevance
“…We chose 455 nm as a compromise excitation wavelength absorbed by the long side of the chlorophyll a (or divinyl chlorophyll a) absorbance band, which is the only pigment present across all our diverse study strains. Emerging multi-spectra chlorophyll fluorometers will support more generalized analyses across multiple excitation bands delivered through different antenna complexes (Simis et al, 2012) across taxa.…”
Section: Methodsmentioning
confidence: 99%
“…We chose 455 nm as a compromise excitation wavelength absorbed by the long side of the chlorophyll a (or divinyl chlorophyll a) absorbance band, which is the only pigment present across all our diverse study strains. Emerging multi-spectra chlorophyll fluorometers will support more generalized analyses across multiple excitation bands delivered through different antenna complexes (Simis et al, 2012) across taxa.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, owing to the differences in light harvesting systems (pigment-protein binding in particular), especially in dinoflagellates and cyanobacteria (see MacIntyre et al, 2010;Millie, Schofield, Kirkpatrick, Johnsen, & Evens, 2002), the peak wavelength of fluorescence depends also on the species composition of phytoplankton. Thus, for example, phycocyanin-rich cyanobacteria have an additional emission peak at~655 nm due to phycocyanin (MacIntyre et al, 2010;Simis, Huot, Babin, Seppälä, & Metsamaa, 2012), which is close to the first chosen baseline for the MODIS algorithm (667 nm). Therefore, in the case of multispectral retrievals the position of spectral bands for the nFLH retrieval can lead to a smaller sensitivity and lower fluorescence values.…”
Section: Comparison With Modis Nflh Datamentioning
confidence: 75%
“…However, it may be that some of the phycobilin pigments tagged along with the lipids during the extraction as in the case of Nodularia harveyana. Simis et al (2012) showed that phycocyanin, which might be mixed with phycoerythrocyanin, is the most abundant photosynthetic accessory pigment. Apart from the chlorophyll pigments, Leptolyngbya spp.…”
Section: Lipid Extractsmentioning
confidence: 99%